Treating ESL Writing Errors: Balancing Form and Content - María Cristina Giraldo de Londoño; Ronald Alan Perry (Asociación Colombiana de Profesores de Ingles, 2008)
The general acceptance of Communicative Language Teaching has generated confusion with respect to the role of writing in the ESL curriculum, the usefulness of ESL writing error treatment, and the form that treatment should take. An imaginary conflict between the goals of encouraging students' communicative use of L2 and that of promoting formal correctness often discourages ESL teachers from dealing with writing errors that may be easily treatable during early stages of learning but which, left untreated, continue to affect students' performance at much higher academic levels. By careful application of appropriate techniques, teachers can provide error treatment while promoting habits of self monitoring, revision, and autonomy.